Comparison between scalpel incision and electrocautery incision in midline abdominal surgery: a comparative study - Yadav, Amit; Agarwal, Lakshman; Jain, Sumit A.; Kumawat, Sanjay; Sharma, Sandeep (International Surgery Journal, 2021)
Background: Fear of poor wound healing have curtailed the use of diathermy for making skin incision. Scalpel produces little damage to surrounding tissue but causing more blood loss. Our aim of study was to compare electrocautery incision with scalpel incision in terms of incision time, blood loss, postoperative pain and wound infection. Methods: Total of 104 patients were included in the study undergoing midline abdominal surgery. Patients were randomized into electrocautery (group A) and scalpel (group B). The incision dimension, incision time and blood loss were noted intraoperatively. Postoperative pain was noted on postoperative day 2 using visual analog scale. Wound complications were recorded on every postoperative day till the patient was discharged. Results: 52 patients in each of the two groups were analyzed. There was significant difference found between group A and group B in terms of mean incision time per unit wound area, 8.16±1.59 s2 and 11.02±1.72 s2 respectively (p value=0.0001). The mean blood loss per unit wound area was found to be significantly lower in group A (0.31±0.04 ml2) as compared to group B (1.21±0.21), p value=0.0001. There was no significant difference noted in terms of postoperative pain and wound infection between both groups. Conclusions: Electrocautery can be considered safe in making skin incision in midline laparotomy compared to scalpel incision with comparable postoperative pain and wound infection with less intraoperative blood loss and less time consuming.